The hippos of Troy why - Tiboni, Francesco, 1976- (Oxford)
iv, 112 sayfa
Keywords: “Deals with one of the most famous episodes of the whole of Classical mythology, the Wooden Horse of Troy. Thanks to the analysis of words, images and wrecks, the author proposes a new interpretation of what Homer actually intended when he spoke of the hippos used by the Greeks to conquer the city of Troy. The archaeological, iconographic and philological evidence discussed by the author leads to the conclusion that Homer never talked about a giant wooden horse, nor a war machine. In fact, Homer referred to the use of a particular ship type, a merchant ship of Levantine origin in use in the Late Bronze Age/Early Iron Age Mediterranean, used to pay tribute to Levantine kings, as well as to trade precious metal around the Mediterranean coast“--